The Thought of Jamaluddin Al-Afghani (Pan-Islamism) and Its Relevance for Contemporary Islamic Education - Atania Firdaus; Havid Yanuardi (Journal of Indonesian Islamic Studies, 2026)
This study aims to analyze the thought of Jamaluddin al-Afghani on Pan-Islamism and its relevance to contemporary Islamic education within the framework of Islamic educational philosophy. Al-Afghani (1839–1897) was a prominent Muslim reformer who responded to the decline of the Muslim world and Western imperialism through the idea of Islamic unity (Pan-Islamism). This research employs a library research method based on primary sources, classical texts, and relevant scholarly literature. Data analysis is conducted using thematic content analysis. The findings indicate that Pan-Islamism is not merely a socio-political movement but also contains a philosophical foundation in Islamic education, particularly through the integration of the concepts of tarbiyah, ta‘lim, and ta’dib. These three concepts form a holistic framework that encompasses intellectual, moral, and spiritual development in education. Al-Afghani emphasized that the revival of the Muslim ummah can only be achieved through education that integrates religious and rational sciences, strengthens critical thinking, and fosters intellectual solidarity among Muslims. In the context of contemporary Islamic education, his thought remains relevant in promoting educational reform that is integrative, progressive, and adaptive to modern challenges while preserving Islamic identity. However, Pan-Islamism also has limitations, particularly its idealistic emphasis on unity, which may overlook socio-cultural and epistemological diversity within the Muslim world.